2004
DOI: 10.1345/aph.1e136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Cognitive, and Neurophysiologic Correlates of Short-Term Treatment with Carbamazepine, Oxcarbazepine, and Levetiracetam in Healthy Volunteers

Abstract: After short-term treatment in healthy volunteers, carbamazepine induced major clinical and neurophysiologic changes. Oxcarbazepine was better tolerated than carbamazepine. Levetiracetam interfered least with clinical and neurophysiologic test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…First, frontal lobe functions including psychomotor speed, attention, mental flexibility, verbal fluency, and executive function improved across the LEV monotherapy. Previous studies reported similar results on frontal lobe function [6,12,18]. Second, there was noticeable improvement on several categories of memory function including both visual and verbal domains.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…First, frontal lobe functions including psychomotor speed, attention, mental flexibility, verbal fluency, and executive function improved across the LEV monotherapy. Previous studies reported similar results on frontal lobe function [6,12,18]. Second, there was noticeable improvement on several categories of memory function including both visual and verbal domains.…”
Section: Discussionsupporting
confidence: 76%
“…We included only drug-naïve epilepsy patients who were not exposed to any AEDs. In previous studies, LEV as an adjunctive treatment may reduce seizure frequency and improve cognitive function [12,15,17]. In those add-on studies, it was difficult to estimate the pure effect of LEV on cognition due to the concomitant use of other AED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 One other study that compared the clinical cognitive, neurophysiologic effects of carbamazepine, oxcarbazepine and levetiracetam in healthy volunteers found that levetiracetam was the most favorable of the 3 for causing the least amount of deficiencies. 71 Paradoxical increases in seizure activity have been reported. 12,[72][73][74] These are believed to occur at higher doses of levetiracetam and in patients with preexisting mental disabilities.…”
Section: Safety Tolerability and Adverse Effectsmentioning
confidence: 99%
“…On the other hand, anticonvulsants can impair cognitive function in healthy volunteers and in patients with brain impairments [74,119]. The negative effects of these drugs in children may persist even after drug withdrawal [69], and babies born to mothers exposed to antiepileptic drugs are at increased risk for major congenital malformations, cognitive impairment and fetal death [8].…”
Section: Introductionmentioning
confidence: 99%